The Spiritual Needs and Resources of Hospitalized Primary Care Patients - Ellis, Mark R. (Journal of religion and health, 2013)
Previous studies have recognized the importance of hospitalized primary care patients' spiritual issues and needs. The sources patients consult to address these spiritual issues, including the role of their attending physician, have been largely unstudied. We sought to study patients' internal and external resources for addressing spiritual questions, while also exploring the physician's role in providing spiritual care. Our multicenter observational study evaluated 326 inpatients admitted to primary care physicians in four midwestern hospitals. We assessed how frequently these patients identified spiritual concerns during their hospitalization, the manner in which spiritual questions were addressed, patients' desires for spiritual interaction, and patient outcome measures associated with spiritual care. Nearly 30% of respondents (referred to as "R/S respondents") reported religious struggle or spiritual issues associated specifically with their hospitalization. Eight-three percent utilized internal religious coping for dealing with spiritual issues. Chaplains, clergy, or church members visited 54% of R/S respondents; 94% found those visits helpful. Family provided spiritual support to 45% of R/S respondents. Eight percent of R/S respondents desired, but only one patient actually received, spiritual interaction with their physician, even though 64% of these patients' physicians agreed that doctors should address spiritual issues with their patients. We conclude that inpatients quite commonly utilize internal resources and quite rarely utilize physicians for addressing their spiritual issues. Spiritual caregiving is well received and is primarily accomplished by professionals, dedicated laypersons, or family members. A significantly higher percentage of R/S patients desire spiritual interaction with their physician than those who actually receive it.